\(\sqrt{2-\sqrt{3}}-\sqrt{4-\sqrt{15}}\)

">
K
Khách

Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.

25 tháng 7 2021

\(\sqrt{2-\sqrt{3}}-\sqrt{4-\sqrt{15}}=\frac{\sqrt{4-2\sqrt{3}}-\sqrt{8-2\sqrt{15}}}{\sqrt{2}}\)

\(=\frac{\sqrt{\sqrt{3}^2-2\sqrt{3}+1}-\sqrt{\sqrt{5}^2-2\sqrt{3}\sqrt{5}+\sqrt{3}^2}}{\sqrt{2}}\)

\(=\frac{\sqrt{\left(\sqrt{3}-1\right)^2}-\sqrt{\left(\sqrt{5}-\sqrt{3}\right)^2}}{\sqrt{2}}\)

\(=\frac{\sqrt{3}-1-\sqrt{5}+\sqrt{3}}{\sqrt{2}}\)

\(=\frac{2\sqrt{3}-1-\sqrt{5}}{\sqrt{2}}\)

22 tháng 7 2016

a) Đặt A=\(\sqrt{4+\sqrt{7}}-\sqrt{4-\sqrt{7}}\)

<=> \(\sqrt{2}\cdot A=\sqrt{8+2\sqrt{7}}-\sqrt{8-2\sqrt{7}}\)=\(\sqrt{\left(\sqrt{7}+1\right)^2}-\sqrt{\left(\sqrt{7}-1\right)^2}\)

\(\sqrt{7}+1-\sqrt{7}+1=2\)

=> \(A=\frac{2}{\sqrt{2}}\sqrt{2}\)

b) Ta đặt \(B=\sqrt{4+\sqrt{10+2\sqrt{5}}}+\sqrt{4-\sqrt{10+2\sqrt{5}}}\)

=> \(B^2=8+2\sqrt{16-\left(10+2\sqrt{5}\right)}\)

             =  \(8+2\sqrt{6-2\sqrt{5}}=8+2\sqrt{5-2\sqrt{5}+1}\)=\(8+2\sqrt{\left(\sqrt{5}-1\right)^2}=8+2\sqrt{5}-2=6+2\sqrt{5}\)

\(5+2\sqrt{5}+1=\left(\sqrt{5}+1\right)^2\)

=>  B=\(\sqrt{5}+1\)

c) Ta xét \(A=\sqrt{4+\sqrt{15}}+\sqrt{4-\sqrt{15}}\)

=> \(\sqrt{2}\cdot A=\sqrt{8+2\sqrt{3}\cdot\sqrt{5}}+\sqrt{8-2\sqrt{3}\cdot\sqrt{5}}\)

                 =  \(\sqrt{\left(\sqrt{3}+\sqrt{5}\right)^2}+\sqrt{\left(\sqrt{5}-\sqrt{3}\right)^2}\)

                =  \(\sqrt{3}+\sqrt{5}+\sqrt{5}-\sqrt{3}\)\(2\sqrt{5}\)

=> A=\(\sqrt{5}\)

Ta có : \(\sqrt{4+\sqrt{15}}+\sqrt{4-\sqrt{15}}-2\sqrt{3-\sqrt{5}}\)

\(A-\sqrt{6-2\sqrt{5}}\)

\(\sqrt{5}-\sqrt{\left(\sqrt{5}-1\right)^2}=\sqrt{5}-\sqrt{5}+1\)=1

22 tháng 7 2016

Phần a) chỗ cuối viết thiếu dấu =.

Sẽ là A=\(\sqrt{2}\)nha

9 tháng 6 2019

a,A.√2= √(4+2√3)-√(4-2√3)

= √(1+√3)2 -√( √3 -1)2

= 1+√3-√3+1= 2 

=> A= 2/√2=√2

9 tháng 6 2019

B2= (4+√15)2.(4-√15).(√10-√6)2

= (4+√15).1.(16-4√15)

= (4+√15).(4-√15).4

= 4

=> B = √4 = 2

18 tháng 5 2019

\(A=\sqrt{4+\sqrt{7}}-\sqrt{4+\sqrt{7}}\Leftrightarrow\sqrt{2}A=\sqrt{8+2\sqrt{7}}-\sqrt{8+2\sqrt{7}}\)

\(\Leftrightarrow\sqrt{2}A=\sqrt{\sqrt{7}^2+2\sqrt{7}+1}-\sqrt{\sqrt{7}^2+2\sqrt{7}+1}\)

\(\Leftrightarrow\sqrt{2}A=\sqrt{7}+1-\sqrt{7}-1=0\)

\(\Leftrightarrow A=0\)

25 tháng 6 2017

a) \(\sqrt{\left(2-\sqrt{3}\right)^2}+\sqrt{4-2\sqrt{3}}\)

= \(2-\sqrt{3}+\sqrt{\left(\sqrt{3}-1\right)^2}\)

\(2-\sqrt{3}+\sqrt{3}-1\) = \(1\)

b) \(\sqrt{15-6\sqrt{6}}+\sqrt{33-12\sqrt{6}}\)

= \(\sqrt{\left(3-\sqrt{6}\right)^2}+\sqrt{\left(3-2\sqrt{6}\right)^2}\)

= \(3-\sqrt{6}+2\sqrt{6}-3\) = \(\sqrt{6}\)

c) \(\left(15\sqrt{200}-3\sqrt{450}+2\sqrt{50}\right):\sqrt{10}\)

= \(\dfrac{15\sqrt{200}}{\sqrt{10}}-\dfrac{3\sqrt{450}}{\sqrt{10}}+\dfrac{2\sqrt{50}}{\sqrt{10}}\)

= \(15\sqrt{20}-3\sqrt{45}+2\sqrt{5}\)

= \(30\sqrt{5}-9\sqrt{5}+2\sqrt{5}\) = \(23\sqrt{5}\)